KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBINAAN KOMPETENSI PEDAGOGIK GURU DI SMANEGERI 1 UNGGUL DARUL IMARAH KABUPATEN ACEH BESAR - Sri Rahmiq; Nurussalami Nurussalami; Devi Yani (Hijri, 2019)
Data collectiontechniques using interviews, observation, and documentation. The results of thisstudy indicate that the leadership style of the headmaster of SMA Negeri 1 DarulImarah has two leadership styles namely, charismatic leadership style anddemocratic leadership style. While the teacher pedagogical competencydevelopment model by the head of Neegri 1 Darul Imarah High School uses themodel of class supervision, workshops, procurement of school meetings, andseminars or training. The obstacles of the head of SMA Negeri 1 Darul Imarah indeveloping teacher pedagogical competence are, the lack of teacher preparation inmaking learning tools, and there are some teachers who lack discipline inattending meetings.